Laparoscopically Treated Giant Gastric Bezoar Complicated with Large Ulcer in Young Patient - Ulusoy, Cemal; Nikolovski, Andrej; Yavuz, Giray; Saydam, Tuba; Demirel , Ali İlbey (Lietuvos chirurgija, 2021)
Gastric bezoars are rare but well known intraluminal formations in the gastrointestinal system. Reports for gastric bezoar treatment include dissolution, endoscopic retrieval and surgery (open and laparoscopic). We are presenting a case of 32 years old male patient presented with giant gastric bezoar complicated with large ulcer. The patient was operated laparoscopically with success. Laparoscopic surgery is safe alternative to open surgery for giant gastric bezoars treatment.